2016
DOI: 10.2220/biomedres.37.187
|View full text |Cite
|
Sign up to set email alerts
|

<b>The selective distribution of LYVE-1-expressing endothelial cells and reticular cells in the reticulo-endothelial system </b><b>(RES) </b>

Abstract: LYVE-1, a receptor molecule for hyaluronan, is expressed in the lymphatic endothelium, blood sinus endothelium, and certain macrophage lineages. The present immunohistochemical study revealed a broader distribution of LYVE-1 in vascular endothelial cells of the murine lung, adrenal gland, and heart as well as the liver and spleen. In addition, sinus reticular cells-including sinuslining cells-in the medulla of the lymph node also intensely expressed LYVE-1. Ultrastructurally, immuno-gold particles for LYVE-1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…Lyve1 -expression is not restricted to the lymphatic vasculature and data presented in this study and by other groups show that LYVE1 is expressed on uncommitted embryonic blood vessels (Gordon et al, 2008). Recent findings show that LYVE1 is expressed on a subset of sinusoidal endothelial cells in the spleen of humans and adult rodents (Banerji et al, 1999; Zheng et al, 2016). LYVE1 is also expressed by resident macrophage populations and a subset of infiltrating macrophages found in tumors and inflamed tissues (Jackson, 2004), and splenic stromal organizer cells during ontogeny (Tan and Watanabe, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Lyve1 -expression is not restricted to the lymphatic vasculature and data presented in this study and by other groups show that LYVE1 is expressed on uncommitted embryonic blood vessels (Gordon et al, 2008). Recent findings show that LYVE1 is expressed on a subset of sinusoidal endothelial cells in the spleen of humans and adult rodents (Banerji et al, 1999; Zheng et al, 2016). LYVE1 is also expressed by resident macrophage populations and a subset of infiltrating macrophages found in tumors and inflamed tissues (Jackson, 2004), and splenic stromal organizer cells during ontogeny (Tan and Watanabe, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…With the use of better antibodies, LYVE-1 expression was also detected in the liver, spleen, and lymph node sinusoidal endothelial cells in humans (Mouta Carreira et al, 2001;Akishima et al, 2004). However, a recent study conducted in rodents has revealed their expression in the non-sinusoidal endothelium of many other organs, such as lungs, heart, and adrenal gland (Zheng et al, 2016). Once regarded as the main receptor responsible for the internalization and transport of HA in the lymph circulation, a study using LYVE-1 KO mice model revealed that it is not crucial for the metabolism of HA in the lymphatic endothelium (Gale et al, 2007).…”
Section: Lyve-1mentioning
confidence: 99%
“…He also developed a new technique for the meningeal lymphatic visualization using the intracisternal injection of mercury. Today Mascagni’s models of the meningeal lymphatic vessels are presented in the Josephinum Wax Models Museum in Vienna [48]. However, Mascagni’s discovery of the meningeal lymphatics was forgotten for two centuries because no one could repeat his experiments due to technical problems.…”
Section: The Gaps In the Lymphatic Anatomy In The Brainmentioning
confidence: 99%